FAKTOR-FAKTOR PENGHAMBAT DALAM PEMBERIAN PEMBEBASAN BERSYARAT TERHADAP NARAPIDANA DI LEMBAGA PEMASYARAKATAN KLAS IIA DENPASAR - Arya Sanjaya Putra, I Gusti Ngurah; Ariawan, I Gusti Ketut; Yusa Darmadi, A. A. Ngurah (Kertha Wicara : Journal Ilmu Hukum, 2013)
One form of development for the inmates in Penitentiary is granting conditional liberation. In practice there are still some constraints in the inplementation. The purpose of this study is to describe and analyze factor of constraint in granting conditional liberation and attempts to minimize those factors. The research applied type of empirical research, of which it moved from the gap between the theories and reality. In Granting Conditional liberation to the inmates there are several inhibiting factors such as the inmates or the person concerned does not have a guarantor and the inmates involved in certain misconduct or other matters that constitute disciplinary offenses thereby granting conditional liberation due to be granted is than delayed. And attempts to minimize the inhibiting factors of granting conditional liberation is by looking for a guarantor for those inmates who do not have a guarantor and optimize development in Penitentiary so that inmates will no longer conduct something lacks of discipline.
Keywords: Penitentiary, conditional liberation, inmates